Reason and Revelation in Ibn Taymiyyah’s Critique of Philosophical Theology: A Contribution to Contemporary Islamic Philosophy of Religion - Adeeb Obaid Alsuhaymi; Fouad Ahmed Atallah (Religions)
This paper addresses the longstanding tension between reason and revelation in Islamic religious epistemology, with a focus on the thought of Ibn Taymiyyah (d. 728/1328). It aims to reassess his critique of philosophical theology (falsafa and kalām) and explore his constructive alternative to rationalist metaphysics. The study adopts a descriptive–analytical methodology, combining close textual reading of Darʾ Taʿāruḍ al-ʿAql wa al-Naql and Naqd al-Manṭiq with conceptual analysis informed by contemporary religious epistemology and philosophy of religion. The findings reveal that Ibn Taymiyyah advances a triadic epistemological model centered on revelation (naql), reason (ʿaql), and innate disposition (fiṭrah). He refutes the autonomy of reason, redefines logic as a tool rather than a judge, and repositions fiṭrah as an intuitive foundation for belief. His approach emphasizes the harmony of sound reason with authentic revelation and challenges the epistemic assumptions of speculative theology. By presenting a comparative table of rationalist and Taymiyyan epistemologies, the study demonstrates how Ibn Taymiyyah’s framework anticipates key themes in Reformed Epistemology and the cognitive science of religion. The conclusions suggest that his vision offers a coherent, theocentric paradigm for religious knowledge that is highly relevant to the contemporary philosophy of religion and Islamic theology.